2019
DOI: 10.1093/jnci/djz093
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy for Colorectal Cancer: A Review of Current and Novel Therapeutic Approaches

Abstract: Colorectal cancer (CRC) remains a leading cause of cancer-related deaths in the United States. Although immunotherapy has dramatically changed the landscape of treatment for many advanced cancers, the benefit in CRC has thus far been limited to patients with microsatellite instability high (MSI-H):DNA mismatch repair–deficient (dMMR) tumors. Recent studies in the refractory CRC setting have led to US Food and Drug Administration approvals for pembrolizumab as well as nivolumab (with or without ipilimumab) for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
117
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(123 citation statements)
references
References 81 publications
0
117
0
Order By: Relevance
“…Despite advances in the understanding of GI cancer biology and in surgery and immunotherapy in recent years, little impact has been made on the mortality associated with advanced GI cancers [15,16,66]. Therefore, there is an unmet need to find new immune-related therapeutic approaches against GI cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite advances in the understanding of GI cancer biology and in surgery and immunotherapy in recent years, little impact has been made on the mortality associated with advanced GI cancers [15,16,66]. Therefore, there is an unmet need to find new immune-related therapeutic approaches against GI cancer.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the DCLK1 expression in these contexts, we performed the CMS analysis of COAD dataset ( Figure 7A). DCLK1 expression was upregulated specifically in the CMS4 which has the worst outcomes among the four subtypes ( Figure 7B) [66]. In addition, we analyzed the CMS subtypes of left-sided and right-sided colon cancers, and found that left-sided colon cancer was more likely to be CMS4 ( Figure 7C).…”
Section: Dclk1 Predicts the Survival Of Patients With Left-sided Colomentioning
confidence: 96%
“…Taken together, our results provide a systematic analysis of the biological changes in the epithelial and stromal compartments of colorectal cancer. Immunotherapy for colorectal cancer is approved only for microsatellite instability-high (MSI-H) patients, which comprise only a small subset (64), by the Food and Drug Administration (FDA). Since the TMB level of colorectal cancer ranks higher than that in other cancers (e.g., TCGA pan-cancer) (65), we have good reason to believe that the prospects for immunotherapy in colorectal cancer are optimistic.…”
Section: Discussionmentioning
confidence: 99%
“…Immunotherapy, particularly ICI, has revolutionized cancer treatment, and although response rates rarely exceed 20%, those who do respond show a durable response [95][96][97]. The responsiveness to ICI was suggested to depend on several key factors, including mutational load (high levels of tumor neoantigens), tumor-infiltrating lymphocytes and regulatory checkpoint receptors.…”
Section: Why Immunotherapy?mentioning
confidence: 99%